PEAC: An Ultrasensitive and Cost-Effective MRD Detection System in Non-small Cell Lung Cancer Using Plasma Specimen - Xu, Jianping; Pu, Yue; Lin, Rui; Xiao, Shanshan; Fu, Yingxue; Wang, Tao (Frontiers in Medicine, 2022)
Circulating tumour DNA (ctDNA), tumour-derived fraction of cell free DNA (cfDNA), has emerged as a promising marker in targeted therapy, immunotherapy, and minimal residual disease (MRD) monitoring in postsurgical patients. However, ctDNA level in early-stage cancers and postsurgical patients is very low, which posed many technical challenges to improve detection rate and sensitivity especially in the clinical practice of MRD detection. Those challenges usually include insufficient DNA input amount, limit of detection (LOD) and high experimental costs. To resolve those challenges, we developed an ultra-sensitive ctDNA MRD detection system in this study, namely PErsonalized Analysis of Cancer (PEAC), to simultaneously detect up to 37 mutations which account for 70%-80% non-small cell lung cancer (NSCLC) driver mutations from low plasma sample volume and enables limit of detection (LOD) of 0.01% at single site level. We demonstrated the high performance achieved by PEAC on both cell-free DNA (cfDNA) reference standards and clinical plasma samples from three NSCLC patient cohorts. For cfDNA reference standards, PEAC achieved a specificity of 99% and a sensitivity of 87% for the mutations at 0.01% allele fraction. In the second cohort, PEAC showed 100% concordance rate between ddPCR and NGS among 29 samples. In the third cohort, 22 of 59 patients received EGFR TKI treatment. Among them, three in four patients identified low level actionable gene mutations only by PEAC had partial responses after targeted therapy, demonstrating high ctDNA detection ability of PEAC. Overall speaking, the developed PEAC system can detect the majority of NSCLC driver mutations using 8-10ml plasma samples, and has the advantages of high detection sensitivity and lower costs compared with the existing technologies such as ddPCR and NGS. Those advantages make PEAC system quite appropriate for ctDNA and MRD detection in early stage NSCLC and postsurgical recurrence monitoring.